Effects of fermented products on performance, faecal pH, Enterobacteriaceae and lactic acid bacteria counts and interrelationships, and plasma cholesterol concentration in rats - Loh, T.; Foo, H.; Tan, S.; Goh, Y.; Shukriyah, M.; Kuﬂi, C. (The Kielanowski Institute of Animal Physiology and Nutrition, PAS, 2003)
Fermented products (FP), a mixed product of raw fish, sea weed, rice bran, sugar cane juice, were obtained in a process of fermentation using combination of cultures of lactic acid bacteria (LAB). The objectives of this study were to assess the effects of diets with different levels of FP on performance, faecal pH, Enterobacteriaceae and LAB counts and their relationships, and plasma cholesterol concentration in rats. A total of 24 Sprague Dawley (10 weeks of age) female rats were assigned individually into three groups of 8 rats per treatment. The three dietary treatments were: 1. control diet (basal diet), 2. basal diet + 10% FP and 3. basal diet + 20% FP. The final liveweight, growth rate, total feed intake and feed conversion ratio were not significantly different for all the treatment groups. Addition of FP to the diets reduced the Enterobacteriaceae population in faeces of the rats and significantly (P<0.05) increased numbers of LAB as compared with control rats. The faecal pH in rats fed with FP was more acidic than in rats fed with basal diet. The correlation analyses between LAB counts and Enterobacteriaceae counts, LAB counts and faecal pH and Enterobacteriaceae counts and faecal pH, suggest that FP provides an acidic environment, which encourages the growth of LAB and then leads to the inhibition of Enterobacteriaceae growth. The plasma cholesterol concentrations for rats fed with FP were significantly lower than that of control rats.